IFPRI strategy: Gender research - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Throughout the developing world, women, working together with men, play the dual roles of agricultural producers and household caregivers and are the key to securing household food security and nutrition. At the same time, the division of rights, resources, and responsibilities between men and women often results in higher vulnerability of women and girls to undernutrition, micronutrient malnutrition, poor health, and a general lack of time to accomplish their daily tasks. As the global community mobilizes in support of Sustainable Development Goal (SDG) 5 on gender equality and women’s rights, at least 11 of the 17 SDGs include indicators related to gender dynamics-the social relations between men and women. SDG2, ending world hunger, explicitly mentions addressing the constraints for women who are small-scale food producers and the nutritional needs of women and adolescent girls. To monitor progress toward these goals, significant global commitments have been made to close the gender data gap. Closing this data gap means paying close attention to gender dynamics in all of IFPRI’s strategic research areas.